The Genesis of Venture Capital - Lessons from the German Experience - Ralf Becker; Thomas Hellmann (Center for Economic Studies and ifo Institute (CESifo), 2003)
Why does venture capital work in some countries but not in others? This clinical study of the first German venture capital firm examines the difficulties of creating a venture capital market in a bank-based financial system. The analysis identifies the problem of creating appropriate governance structures to protect investor returns. It exposes the difficulties of established banks - not to mention government - to devise venture investment strategies. It identifies the availability of high quality entrepreneurs as a critical complement. And it provides a reinterpretation of the hypothesis of Black and Gilson (1997), arguing that the existence of an active stock market is a necessary, but by no means sufficient condition for the development of venture capital.
Keywords: 330